Identification of Suitable Solid Waste Disposal Site by Using GIS Based Multi Criteria: a Case Study of Adama Town, Ethiopia - Eyerus Gebregiorgis Gebremedhin; Andinet Kebede Tekile; Daniel Reddythota (Geology, Ecology, and Landscapes)
The objective of this research was to investigate existing waste disposal practices and to determine the optimally suitable and acceptable disposal site for Adama town, Ethiopia. The pertinent restrictions identified to realize the objective were slope, river proximity, road, soil type, environmentally sensitive areas, protected zone, and settlement proximity. The criteria were weighted in the GIS environment and then, based on appropriateness of dumping places, the region was classified to different suitability zones. The primary stage solid waste collection is carried out by small and micro enterprises (SMEs) and their service covers more than three-fourth of the households of the town. The waste which is not collected by SMEs is mainly disposed of in environmentally sensitive places. According to the results, only 8.64% (939 ha) of the total area is highly suitable, 27.83% (3026 ha) is completely unsuitable and the remaining 63.53% (6908 ha) is moderately suitable. Four municipal solid waste disposal sites with minimum destructive effects and the lowest environmental impacts are identified to be suitable for Adama Town. Thus, the use of GIS for suitable dumping site location was effective, and the findings will be valuable in maintaining healthy environment and public by realizing dumping plants on the identified site.